GENE EXPRESSION of blaOXA-51-like and blaOXA-23 in RESPONSE to β-Lactam ANTIBIOTIC IN CLINICALLY ISOLATED ACINETOBACTER BAUMANNII AND ACINETOBACTER LOWFFII FROM URINE SAMPLES - Al-Haideri, H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
In this study, two isolates A. lowffii, and A. baumannii were obtained clinically, and genomically identified by 16S rRNA assessment with the accession number (MH685113.1 and MH685112.1) for A. lowffii and A. baumannii respectively. The sensitivity profile of the isolates was variable, and A. baumannii was the most resistant strain towards a wide range of antibiotics, and it did not show any growth defect in the presence of β-lactam antibiotic, in comparison with A. lowffii. We identified that the blaOXA-23 gene was responsible for imipenem resistance in A. baumannii, whereas, blaOXA-51-like was moderately confer resistance towards A. lowffii which lack of blaOXA-23. This was determined when the isolates were subjected to qRT-PCR. We identified that the blaOXA-23 gene was increased about 1-fold in the presence of imipenem, whereas, blaOXA-51-like did not increased in comparison to the control. Bioinformatic analyses revealed that blaOXA-23 is located in the cytoplasm, and blaOXA-like 51 is located in the periplasm. Our hypothesis suggests that blaOXA-23 gene have a major contribution in the outbreak of multidrug resistance Acinetobacter species.